Pengaruh Entrepreneurial Marketing dan Kebijakan Pemerintah terhadap Daya Saing Industri Alas Kaki di Bogor - Stevia Septiani; Ma'mun Sarma; Wilson H. Limbong (Jurnal Manajemen dan Organisasi, 2013)
Entrepreneurial marketing is the suitable approach in terms of resource constraints and problems that exist in small and medium enterprises (SMEs). Footwear industry is a sector of Small and Medium Enterprises (SMEs) that is supported by the government of Bogor. Problems of development of footwear industry are divided into two main factors: the competence of SMEs and local government policy. Based on these problems, this study aims to (1) Identify the characteristics of entrepreneurs, business characteristics and linkages both of them, (2) Identify and analyze the ability of entrepreneurial marketing, implementation of government policies and the ability of the competitiveness of small industrial footwear in Bogor, and (3) Identify and analyze the influence of entrepreneurial marketing and government policies on the competitiveness of the footwear industry in Bogor. Sample selection is done by purposive cluster sampling method. The samples in this study were 100 small business owners. This study employs three data analysis: descriptive analysis, index transformation analysis, and analysis of structural equation modeling (SEM) with partial least square (PLS). Characteristics of footwear SME owners in Bogor is included the low-educated group. However, they have excellent expertise in the producing of footwear. Characteristics of footwear enterprises in Bogor, is categorized as the long standing and major businesses. Based on the analysis of SEM with PLS approach, it is known that the entrepreneurial marketing variables have a positive impact on the competitiveness of small industrial footwear in Bogor, while the government policies variables have an indirect effect on competitiveness through entrepreneurial marketing variables.Keyword: entrepreneurial marketing, competitiveness, SMEs, footwear industry, PLS